24,25,26 is a pythagorean triplet. True or fals​

Answers

Answer 1
Answer:

Step-by-step explanation:

for this the Pythagoras equation must be true :

c² = a² + b²

c is the Hypotenuse the dude opposite of the right angle in a right-angled triangle.

as such it had to be the longest side.

so, c = 26

and we get

26² = 24² + 25²

676 = 576 + 625 = 1201

wrong, 1201 is not equal to 676, so, 24, 25, 26 are NOT a pythagorean triplet.

theinitialstatementisfalse.


Related Questions

Which image (A'B'C'D') of ABCD cannot be produced using only reflection?
Am I corectWhat is the fraction 8/36 expressed in lowest terms? I got 2/9 thats my final answer
Bella is 10 5/12 years old. Franco is 12 7/12 years old. What is the difference in their ages? Write in simplest form.
Jenny decides to save her babysitting money for her college education instead of using it to buy a new outfit. Jenny's choice is an example of which of the following economic principles? Select the best answer from the choices provided. a cost-benefit analysis the law of supply the law of demand a trade-off NextReset]
Translate the algebraic expression shown below into a verbal expression.x/4 The sum of four and some number The product of some number and four The difference of four and some number The quotient of some number and four

The pair of points( 6 ,y) and (10, -1) lie on a line with slope 1/4. What is the value of y?

Answers

We know that general formula for the line is y=ax+b, we know that a=1/2. To get b we can subsittute x=10 and y=-1 (from the second point)
-1=1/2*10+b
-1=5+b     /-5
-6=b
We know that our line is y=1/2x-6
Now we can substitute x=6 (from first point) and find value of y
y=1/2*6-6
y=3-6
y=-3 - its the answer

Hi can someone help me ty happy holiday days

Answers

Answer:

128 ,  512,  2048

Step-by-step explanation:

Which are vertical angels?

Answers

Answer:

Those angles are in opposite either in vertical or horizontal. They are opposite angles

what are the solution(s) to the quadratic equation 50 – x2 = 0? x = ±2 x = ±6 x = ±5 no real solution

Answers

Consider the given quadratic equation 50-x^2=0

x^2-50=0

Comparing the given quadratic equation to the general equation ax^2+bx+c=0, we get a= 1, b=0 and c= -50

So, the solution to the quadratic equation is given by:

x = (-b \pm √(b^2-4ac))/(2a)

x = (-0 \pm √(0^2-4(1)(-50)))/(2)

x = (\pm √(200))/(2)

x = \pm \sqrt2 (5)

x = \pm 5\sqrt2

So, the solutions to the given quadratic equation are x = \pm 5\sqrt2.

Answer:

c

Step-by-step explanation:

.......................

What is 2/5 of 20???

Answers

(2)/(5)\ of\ 20\Rightarrow(2)/(5)*20=(2)/(5)*(20)/(1)=(40)/(5)=8
2/5 of 20 = 20/5 * 2 = 4 * 2 = 8

How many roots do the following equations have? -12x^2 - 25x+5 +x^3=0

Answers

Answer:

There are 3 roots of the given equation.

Step-by-step explanation:

Given the equation      

-12x^2-25x+5+x^3=0

we have to tell the number of roots of the given equation.

As the number of roots for an equation is equal to degree.

The degree of a polynomial is the highest power of its monomials  with non-zero coefficients.

Hence, number of roots is the highest power in the equation.

Now, the equation is -12x^2-25x+5+x^3=0

The highest power i.e degree of equation is 3.

hence, there are 3 roots of the given equation.

-12x^2 - 25x + 5 + x^(3) = 0
x^(3) - 12x^(2) - 25x + 5 = 0
x = \sqrt[3]{((-b^(3))/(27a^(3)) + (bc)/(6a^(2)) - (d)/(2a)) + \sqrt{((-b^(3))/(27a^(3)) + (bc)/(6a^(2)) - (d)/(2a))^(2) + ((c)/(3a) - (b^(2))/(9a^(2)))^(3)}} + \sqrt[3]{((-b^(3))/(27a^(3)) + (bc)/(6a^(2)) - (d)/(2a)) - \sqrt{((-b^(3))/(27a^(3)) + (bc)/(6a^(2)) - (d)/(2a))^(2) + ((c)/(3a) - (b^(2))/(9a^(2)))^(3)}} - (b)/(3a)
x = \sqrt[3]{((-(-12)^(3))/(27(1)^(3)) + ((-12)(-25))/(6(1)^(2)) - (5)/(2(1))) + \sqrt{((-(-12)^(3))/(27(1)^(3)) + ((-12)(-25))/(6(1)^(2)) - (5)/(2(1)))^(2) + ((-25)/(3(1)) - (-(-25)^(2))/(9(1)^(2)))^(3)}} + \sqrt[3]{((-(-12)^(3))/(27(1)^(3))}} + ((-12)(-25))/(6(1)^(2)) - (5)/(2(1))) - \sqrt{((-(-12)^(3))/(27(1)^(3)) + ((-12)(-25))/(6(1)^(2)) - (5)/(2(1)))^(2) + ((-25)/(3(1)) - (-(-25)^(2))/(9(1)^(2)))^(3) - (-12)/(3(1))}}
x = \sqrt[3]{((-(-1728))/(27(1)) + (300)/(6(1)) - (5)/(2)) + \sqrt{((-(-1728))/(27(1)^(3)) + (300)/(6(1)) - (5)/(2))^(2) + ((-25)/(3(1)) - (144)/(9(1)))^(3)}}} + \sqrt[3]{((-(-1728))/(27(1)) + (300)/(6(1)) - (5)/(2)) - \sqrt{((-(-1728))/(27(1)^(3)) + (300)/(6(1)) - (5)/(2))^(2) + ((-25)/(3(1)) - (144)/(9(1)))^(3)}}} - (-12)/(3)
x = \sqrt[3]{((1728)/(27) + (300)/(6) - 2(1)/(2)) + \sqrt{((1728)/(27) + (300)/(6) - 2(1)/(2))^(2) + ((-25)/(3) - (144)/(9))^(3)}} + \sqrt[3]{((1728)/(27) + (300)/(6) - 2(1)/(2)) - \sqrt{((1728)/(27) + (300)/(6) - 2(1)/(2))^(2) + ((-25)/(3) - (144)/(9))^(3)}} - 4
x = \sqrt[3]{(64 + 50 - 2(1)/(2)) + \sqrt{(64 + 50 - 2(1)/(2))^(2) + (-8(1)/(3) - 16)^(3)}} + sqrt[3]{(64 + 50 - 2(1)/(2)) - \sqrt{(64 + 50 - 2(1)/(2))^(2) + (-8(1)/(3) - 16)^(3)}} - 4
x = \sqrt[3]{(114 - 2(1)/(2)) + \sqrt{(114 - 2(1)/(2))^(2) + (-24(1)/(3))^(3)}} + \sqrt[3]{(114 - 2(1)/(2)) - \sqrt{(114 - 2(1)/(2))^(2) + (-24(1)/(3))^(3)}} - 4
x = \sqrt[3]{(112(1)/(2)) + \sqrt{(112(1)/(2))^(2) - (24(1)/(3))^(3)}} - \sqrt[3]{(112(1)/(2)) + \sqrt{(112(1)/(2))^(2) - (24(1)/(3))^(3)}} - 4
x = \sqrt[3]{112(1)/(2) + √(12656.25 - 14408.037)} + \sqrt[3]{112(1)/(2) + √(12656.25 - 14408.037)} - 4
x = \sqrt[3]{112(1)/(2) + √(-1751.787)} + \sqrt[3]{112(1)/(2) - √(-1751.787)} - 4
x = \sqrt[3]{112(1)/(2) + 41.855i} + \sqrt[3]{112(1)/(2) - 41.855i} - 4
x = -4 + \sqrt[3]{112(1)/(2) + 41.855i} + \sqrt[3]{112(1)/(2) - 41.855i}